2022
DOI: 10.1002/solr.202200714
|View full text |Cite
|
Sign up to set email alerts
|

Decorating Phosphorus‐Doped g‐C3N4 with Zinc Porphyrin Metal–Organic Framework via an Electrostatic Self‐Assembly Process: An Efficient Strategy to Boost Photocatalytic Hydrogen Evolution Performance

Abstract: Herein, a novel 2D/2D heterostructure, phosphorus‐doped carbon nitride nanosheet/zinc porphyrin metal–organic framework (MOF) (HPCNN/ZnPMOF), is elaborately fabricated through an electrostatic self‐assembly process for photocatalytic H2 evolution from water splitting. The as‐prepared HPCNN/ZnPMOF 2D/2D photocatalyst displays the highest H2 evolution rate of 65.3 mmol g−1 h−1 under simulated solar irradiation, which is 2.2 and 49.1 times higher than that of HPCNN and ZnPMOF, respectively. The enhanced photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The fundamentals of heterojunctions can be found elsewhere. 82,83 In this context, several heterojunctions using PMOFs with other inorganic materials like TiO 2 , 86 titanate nanotubes (TNTs), 87 ZnIn 2 S 4 , 88 Nb 6 O 17 , 89 and CdS 90 and recently using metal-free materials such as carbon nitrides 84,85 and covalentorganic frameworks (COFs) 91,92 were reported. Table 2 summarizes the results in terms of photocatalytic activity/stability.…”
Section: Photocatalytic Her Using Pmof Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamentals of heterojunctions can be found elsewhere. 82,83 In this context, several heterojunctions using PMOFs with other inorganic materials like TiO 2 , 86 titanate nanotubes (TNTs), 87 ZnIn 2 S 4 , 88 Nb 6 O 17 , 89 and CdS 90 and recently using metal-free materials such as carbon nitrides 84,85 and covalentorganic frameworks (COFs) 91,92 were reported. Table 2 summarizes the results in terms of photocatalytic activity/stability.…”
Section: Photocatalytic Her Using Pmof Compositesmentioning
confidence: 99%
“…In recent years, a couple of studies have been reported on the development of 2D/2D heterojunctions based on PMOFs and carbon nitride (CN)-based materials for the HER. 84,85 One of the intrinsic properties of these 2D/2D heterojunctions is to facilitate the interface contact between the counterparts and, thus, the photocatalytic activity. Similarly, some studies have described the possibility of preparing MOF/COF composite photocatalysts.…”
Section: Photocatalytic Her Using Pmof Compositesmentioning
confidence: 99%
“…[7][8][9][10] The primary advantage of porphyrins in photocatalytic applications lies in their wide absorption of light from ultraviolet to visible light, presenting the potential for comprehensive utilization of solar energy. 11,12 Meanwhile, the chemical and physical properties of porphyrins can be easily modulated through substitution, to provide appropriate electron transfer pathways for various photocatalytic reactions. 13,14 Meso-substitution is more favorable and feasible for porphyrins relative to b-substitution, and is often used to modulate the properties of porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the performance by constructing reasonable heterojunctions may be an important means to develop the application of graphdiyne in photocatalytic hydrogen production. 20 Graphitic phase carbon nitride (g-C 3 N 4 ) has attracted a lot of attention as a non-metallic semiconductor catalyst since it became available. 21 It has a suitable band gap, stable chemical properties as well as inexpensive raw materials and simple preparation, showing excellent applicability in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the performance by constructing reasonable heterojunctions may be an important means to develop the application of graphdiyne in photocatalytic hydrogen production. 20…”
Section: Introductionmentioning
confidence: 99%